China's Confucius Institute in Africa: a different story?. Issue 4 (1st July 2021) - Li, Siyuan
Abstract : Purpose: China's Confucius Institutes (CIs) have been under increasing scrutiny in the West while their development in Africa has been steady and strong. This article aims to examine the establishment, operation and effects of this institute in Africa, and discuss its role in a wider context of education, development and China's foreign policy towards Africa. Design/methodology/approach: This empirical research is a case study of China's Confucius Institutes in Africa. Fieldwork data was collected in China and seven CIs in four African countries. Findings: This research found that the CIs were not just Chinese language and culture promotion organisations in Africa. Rather, they played a deeper and more profound role in training local individuals, involving them in different forms of Chinese presence in Africa and linking their own personal development with the rise of China. In that sense, this article argues that the CI plays a positive role in promoting China's soft power and national interest in Africa. This article also highlights the problems of the institute's operational mode, and casts doubt on some aspects of its future development. Originality/value: This research systematically examines the establishment, operation and effects of the CIs in Africa, in an attempt to understand the real role of this institute in China's foreign policy towards Africa and demonstrate the uniqueness of the situation of the CIs in Africa.